PENGARUH PEMBELAJARAN SETS PADA KEMAMPUAN BERPIKIR KRITIS SISWA SMA - Rasyidi, Mulia (LPPM Institut Pendidikan Nusantara Global, 2020)
The purpose of this study was to determine the effect of SETS (Science, Environment, Technology, Society) learning on the mastery of students' critical thinking abilities using tests and observations. The type of this research was a quasi experiment. This research used an experimental class and control class. The sampling technique used was cluster sampling. To determine the differences in the mastery of critical thinking skills in the control class and the experimental class, the t-test was carried out with the Polled Variance formula. The analysis results show t count = 10.1332 while t table = 1.9908 with a significant level of 0.05 so that t count> t table. H1 is accepted, it can be the influence of the SETS (Science, Environment, Technology and Society) learning method on critical thinking skills. So that can be conclude that there is an influence of the SETS learning method in improving students' critical thinking skills.